Women’s Electability in the 2019 Legislative Elections in Kulon Progo Regency - Dian Eka Rahmawati; Devi Syahfitri (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2021)
Women's representation is indispensable in the policy making process related to women's interests and needs. Kulon Progo Regency is the only regency in DIY Province that has increased the number of female candidates elected in the 2019 legislative elections. This study aims to analyze the factors that influence women's elections in Kulon Progo Regency in the 2019 legislative elections. This study uses qualitative methods. Data collection is done by documentation and interview techniques. The results showed that there had been an increase in the selection of female candidates by 2.5% compared to the 2014 legislative elections. Factors supporting women's electability: family support, social skills, education and political experience, support from political parties, and solidity of the success team. Inhibiting factors for women's electability: competition with incumbents, lack of education and political experience, open proportional electoral systems, limited funds, and limited campaign time.